If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 11 + -6x + -21 = 2 Reorder the terms: 11 + -21 + 3x + -6x = 2 Combine like terms: 11 + -21 = -10 -10 + 3x + -6x = 2 Combine like terms: 3x + -6x = -3x -10 + -3x = 2 Solving -10 + -3x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -3x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = 2 + 10 -3x = 2 + 10 Combine like terms: 2 + 10 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 3(6x-5)=6(x+4)-3 | | 5(-8x+12)= | | x^2+100=x^2+16 | | 4y=19+-7x | | (4)x=20 | | 2y-12=8 | | 0.95X+0.05(10-x)=0.10(-31) | | 2wp=p | | -7x^2-55x-42= | | 7x-4y=19fory | | 3-3a=12 | | X^3-12X^2+4X-30= | | 2w+13=49 | | 2wy=p | | 4.9x^2=-5 | | 2(x-1)+3x=-2 | | 5x-9x=44-16 | | 4x+160y=136 | | 5x-9=44-16 | | (x+5)(x-5)(4x-8)=0 | | 180=(3x-70) | | 3x-6x=1 | | 64=10x-6 | | -(7+x)= | | a=(5a-6) | | 3(x+2)+4(x-5)=10(x+4) | | -9=(-10) | | 4c-6whenc=3 | | a=(3a-7) | | 6(x+16)= | | (5x+2)(5x+2)=144 | | X-8=-4-26 |